Ketahanan Tujuh Varietas Tomat terhadap Nematoda Puru Akar (Meloidogyne spp.) - Lilis Irmawatie; Raden Rubi Robana; Nuraidah Nuraidah (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2019)
Tomato is an annual plant that has high vitamin content and it was widely used by the general people and industry. At present the productivity is still low. One of the causes is the attack of Meloidogyne. The objective of this research was to test resistance of several tomatoe varieties to root knot nematodes (Meloidogyne spp.). Seven tomato varieties had been tested for resistance to Meloidogyne. Plants that were 45 days after planting in a polybag containing 5 kg of soil were infested with second stage larvae (L2). The parameters observed were plant height, number of knots, final population, fruit weight and canopy wet weight and root wet weight. The results showed that none of the tomatoe varieties tested were resistant to Meloidogyne. But there were differences in responses to the Meloidogyne attack including the Ratna variety and Diamond variety showing the lower number of knot and the final population Meloidogyne.